2006
DOI: 10.1002/hlca.200690239
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Pentafluorophenylation of 2,2,3,3,5,6,6-Heptafluoro-3,6-dihydro-2H-1,4-oxazine with an Organosilicon Reagent: NMR and DFT Structural Analysis of Oligo(perfluoroaryl) Compounds

Abstract: F 5 ) was used for the preparation of a series of perfluorinated, pentafluorophenyl-substituted 3,6-dihydro-2H-1,4-oxazines (2 -8), which, otherwise, would be very difficult to synthesize. Multiple pentafluorophenylation occurred not only on the heterocyclic ring of the starting compound 1 (Scheme), but also in para position of the introduced C 6 F 5 substituent(s) leading to compounds with one to three nonafluorobiphenyl (C 12 F 9 ) substituents. While the tris(pentafluorophenyl)-substituted compound 3 could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Lines connect pairs of non-equivalent spins in A m X n spin systems F-C-Cl or F-C-C-Cl arrangement (quite common in chlorofluorocarbons). The reference compound (CFCl 3 ) is known to exhibit a three-line signal due to isotope shifts between isotopomers differing in 35 Cl/ 37 Cl content, so that criticisms have been leveled at its suitability as a reference signal. Computational predictions of such isotope shifts [40] are of the order of 20 ppm for 19 F in CFCl 3 ; however, experimental measurements in several chlorofluorocarbons have shown that such shifts give rise to easily detectable splittings, but amount to no more than 5-7 ppb when F and Cl are separated by 2 bonds [111].…”
Section: General Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lines connect pairs of non-equivalent spins in A m X n spin systems F-C-Cl or F-C-C-Cl arrangement (quite common in chlorofluorocarbons). The reference compound (CFCl 3 ) is known to exhibit a three-line signal due to isotope shifts between isotopomers differing in 35 Cl/ 37 Cl content, so that criticisms have been leveled at its suitability as a reference signal. Computational predictions of such isotope shifts [40] are of the order of 20 ppm for 19 F in CFCl 3 ; however, experimental measurements in several chlorofluorocarbons have shown that such shifts give rise to easily detectable splittings, but amount to no more than 5-7 ppb when F and Cl are separated by 2 bonds [111].…”
Section: General Issuesmentioning
confidence: 99%
“…Some early computational work (aimed at benchmarking and validation) included F 2 as test molecule, which proved to be challenging [26][27][28]. Interest in modeling 19 F shifts has steadily continued, and several papers have appeared in the last decade aimed at general structural issues, solution chemistry and physical organic chemistry, [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] solid-state issues (especially the prediction of chemical shift tensors), [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] J-couplings [65][66][67][68][69][70][71][72]…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in both the previously reported results and in the cases presented here, it is considered that adventitious water molecules attacked the C 6 F 5 Si(CH 3 ) 3 in the presence of a catalytic amount of fluoride anion before the reaction of perfluoroarenes with C 6 F 5 Si(CH 3 ) 3 ; then, the hydrogenation product C 6 F 5 H reacted with another [ ( S c h e m e _ 2 ) T D $ F I G ] molecule of C 6 F 5 Si(CH 3 ) 3 resulting in the formation of p-H(C 6 F 4 ) n F (8f). The electronegative substituent stabilizes the additionelimination intermediate proposed in our previous report [18]; therefore, the intermediate easily formed before the hydrogenation of C 6 F 5 Si(CH 3 ) 3 to prevent the formation of C 6 F 5 H and p-H(C 6 F 4 ) n F.…”
Section: Resultsmentioning
confidence: 96%
“…Although these perfluorinated oligo(phenylene)s 2a-4a have been reported previously [6,14], detailed assignments of 19 F NMR peaks have not been established. We assigned the 19 F NMR peaks of linear perfluoroaryl compound 2a-4a using a 19 F-19 F homodecoupling method and employed the assignments of our previous study [18]. In similar fashion to 1a, octafluorotoluene (1b) provided linear perfluoroaryl derivatives 2b, 3b, and 4b by the terminal position attack of C 6 F 5 Si(CH 3 ) 3 (Table 1, Entries 4 and 5).…”
Section: Resultsmentioning
confidence: 99%
“…A transfer reagent of a fluorinated substituent, C 6 F 5 Si(CH 3 ) 3 , which is prepared by the reaction of C 6 F 5 Br, ClSi(CH 3 ) 3 , and P[N(CH 3 ) 2 ] 3 , was known as a useful pentafluorophenylating reagent for the preparation of perfluoroolefins, perfluoroazaalkenes, or perfluorinated carbonyl compounds . We have reported that the reaction of perfluorinated 3,6‐dihydro‐2 H ‐1,4‐oxazine with C 6 F 5 Si(CH 3 ) 3 provided a series of perfluorinated perfluoroaryl‐substituted 3,6‐dihydro‐2 H ‐1,4‐oxazines . Multiple pentafluorophenylation occurred not only on the heterocyclic ring of the oxazine ring, but also in the para position of the introduced C 6 F 5 substituent(s) leading to the compounds with one to three nonafluorobiphenyl (C 12 F 9 ) substituents.…”
Section: Introductionmentioning
confidence: 99%